2014
DOI: 10.1002/aic.14615
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic CO2 adsorption performance of internally cooled silica‐supported poly(ethylenimine) hollow fiber sorbents

Abstract: The dynamic adsorption behavior of CO2 under both nonisothermal and nearly isothermal conditions in silica supported poly(ethylenimine) (PEI) hollow fiber sorbents (Torlon®‐S‐PEI) is investigated in a rapid temperature swing adsorption (RTSA) process. A maximum CO2 breakthrough capacity of 1.33 mmol/g‐fiber (2.66 mmol/g‐silica) is observed when the fibers are actively cooled by flowing cooling water in the fiber bores. Under dry CO2 adsorption conditions, heat released from the CO2‐amine interaction increases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
67
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 63 publications
(71 citation statements)
references
References 61 publications
(144 reference statements)
2
67
0
Order By: Relevance
“…The results demonstrate that fiber adsorbents exhibited excellent stability in the presence of NO. This result is consistent with previously reported results for amine-based adsorbents [11,13,14,32]. Also, the CO 2 capacity remained nearly constant over 120 cycles, revealing that detectable amine leaching did not occur in these adsorbents, as the amine groups are covalently bonded to the silica surface.…”
Section: Cyclic Stability Of Primary Amine Adsorbent Ca-s-apssupporting
confidence: 94%
See 2 more Smart Citations
“…The results demonstrate that fiber adsorbents exhibited excellent stability in the presence of NO. This result is consistent with previously reported results for amine-based adsorbents [11,13,14,32]. Also, the CO 2 capacity remained nearly constant over 120 cycles, revealing that detectable amine leaching did not occur in these adsorbents, as the amine groups are covalently bonded to the silica surface.…”
Section: Cyclic Stability Of Primary Amine Adsorbent Ca-s-apssupporting
confidence: 94%
“…The composite polymer/silica/amine fiber adsorbents studied in this work are a new type of CO 2 capture platform [28,29] and hold promise for use as practical structured adsorbers [30]. High adsorption capacity [28], fast adsorption kinetics [31,32], and low power plant parasitic loads [33] have been associated with this type of structured adsorbent in the past. In our recent study [32], we demonstrated that 40% of the adsorption capacity in PEI impregnated silica fiber adsorbents (Torlon-S-PEI) was retained after 120 cycles upon exposure to 200 ppm SO 2 .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The high amine efficiency observed here could be partially attributed to the optimized hierarchical structure of the sorbent as well as the reaction mechanism of amine and CO 2 , where the formation of bicarbonates in the presence of moisture rather than carbamates in dry CO 2 theoretically enhances the efficiency of the primary and secondary amines from 0.5 to 1. In addition, the adsorbed water may serve as a plasticizer lowering the CO 2 diffusion resistance and further improving the amine efficiency 31 .…”
Section: Resultsmentioning
confidence: 99%
“…Polymeric-amine coatings have been widely studied due to their high selectivity towards CO 2 and high thermal stability [32,33]. Among all of the amines, polyethyleneimine (PEI) is a widely available and economical amine molecule [34][35][36]. To develop an economical and viable CO 2 adsorption system, a glass fiber that was 7 m in diameter was introduced as a supporting substrate for polyethyleneimine.…”
Section: Introductionmentioning
confidence: 99%